2014
DOI: 10.1158/1078-0432.ccr-13-2265
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Molecular Differences in Prostate Cancer between African American and Caucasian Men

Abstract: Purpose To compare the frequency of ERG rearrangement, PTEN deletion, SPINK1 overexpression, and SPOP mutation in prostate cancer in African American and Caucasian men. Experimental design Dominant tumor nodules from radical prostatectomy specimens of 105 African American men (AAM) were compared to 113 dominant nodules from Caucasian men (CaM). Clinical and pathologic characteristics of the two groups were similar. SPINK1 overexpression was evaluated by immunohistochemistry, ERG rearrangement and PTEN deleti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 47 publications
14
128
3
2
Order By: Relevance
“…Given that the TCGA data set comprises higher frequencies of Gleason 8 and higher tumors in comparison to the AAPC cohort, these copy number differences were less pronounced when stratified by Gleason score yet persisted at certain loci (Supplemental Table 3 and Supplemental Figure 2). For example, overall, PTEN deletions were more common in the TCGA cohort (32%) compared to the AAPC cohort (6%), consistent with previous reports, and this difference remained when examining Gleason 7 and Gleason 8 (or higher) tumors (Supplemental Figure 2) (2). We note that focal copy number gains at 17q25.3, a locus containing the gene fatty acid synthase ( FASN ) and a significant amplification by GISTIC analysis in the AAPC cohort, occur in 12.7% of AAPC tumors in contrast to 1% in the TCGA dataset (p = 0.0001, Fisher’s exact test; Supplemental Figures 1B and 3) (14,15).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Given that the TCGA data set comprises higher frequencies of Gleason 8 and higher tumors in comparison to the AAPC cohort, these copy number differences were less pronounced when stratified by Gleason score yet persisted at certain loci (Supplemental Table 3 and Supplemental Figure 2). For example, overall, PTEN deletions were more common in the TCGA cohort (32%) compared to the AAPC cohort (6%), consistent with previous reports, and this difference remained when examining Gleason 7 and Gleason 8 (or higher) tumors (Supplemental Figure 2) (2). We note that focal copy number gains at 17q25.3, a locus containing the gene fatty acid synthase ( FASN ) and a significant amplification by GISTIC analysis in the AAPC cohort, occur in 12.7% of AAPC tumors in contrast to 1% in the TCGA dataset (p = 0.0001, Fisher’s exact test; Supplemental Figures 1B and 3) (14,15).…”
Section: Resultssupporting
confidence: 88%
“…To extend the finding of ERF copy number loss, we assessed three prostate cancer cohorts for ERF deletion by FISH analysis. Only 1 of 105 cases of localized prostate cancer in African-Americans in a previously published cohort demonstrated hemizygous ERF deletion (2). None of 33 cases of localized prostate cancer in the predominantly white Early Detection Research Network (EDRN) cohort showed deletion in ERF .…”
Section: Resultsmentioning
confidence: 98%
“…Several studies have highlighted molecular differences in PCa in AA and Caucasian men [22] including prevalence of transmembrane protease, serine 2/v-ets avian erythroblastosis virus E26 oncogene homolog (TMPRSS2-ERG) fusions [23] and phosphatase and tensin homolog (PTEN) deletions [24], and gene expression patterns [25]. Studies also suggest that increased androgen signaling is seen in AA men [26].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the association of PTEN loss with lethal events among ERG fusion-negative tumors was much stronger than that seen for PTEN loss considered without ERG status, and this association remained strong even when considering tumors with heterogeneous PTEN loss. Finally, white men primarily comprise our cohort (97%), so our results may not be generalizable to other racial/ethnic groups, in which ERG expression and PTEN loss may be less frequent (45)(46)(47)(48)(49)(50).…”
Section: Articlementioning
confidence: 99%